Областная олимпиада по математике, 2000 год, 9 класс


Докажите равенство $$ \frac{{\left( {1^4 + \frac{1} {4}} \right)\left( {3^4 + \frac{1} {4}} \right)\left( {5^4 + \frac{1} {4}} \right) \dots \left( {11^4 + \frac{1} {4}} \right)}} {{\left( {2^4 + \frac{1} {4}} \right)\left( {4^4 + \frac{1} {4}} \right)\left( {6^4 + \frac{1} {4}} \right) \dots \left( {12^4 + \frac{1} {4}} \right)}} = \frac{1} {{313}}. $$
посмотреть в олимпиаде

Комментарий/решение:

  0
2017-03-26 01:22:13.0 #

$$\prod \limits_{i=1}^{6}{\frac{(2k-1)^4+\frac{1}{4}}{(2k)^4+\frac{1}{4}}}=\frac{1}{313}$$

$$=\prod \limits_{i=1}^{6}{\frac{(2k-1)^4+\frac{1}{4}}{(2k)^4+\frac{1}{4}}}=\prod \limits_{i=1}^{6}{\frac{(2k-1)^4+2\cdot \frac{1}{2}\cdot (2k-1)^2+\frac{1}{4}-(2k-1)^2}{(2k)^4+2\cdot \frac{1}{2}\cdot (2k)^2+\frac{1}{4}-(2k)^4}}=$$

$$=\prod \limits_{i=1}^{6}{\frac{\left((2k-1)^2+\frac{1}{2}\right)^2-(2k-1)^2}{\left((2k)^2+\frac{1}{2}\right)^2-(2k)^2}}=$$

$$=\prod \limits_{i=1}^{6}{\frac{\left((2k-1)^2-(2k-1)+\frac{1}{2}\right) \cdot \left((2k-1)^2+(2k-1)+\frac{1}{2}\right)}{\left((2k)^2-2k+\frac{1}{2}\right) \cdot \left((2k)^2+2k+\frac{1}{2}\right)}}=$$

$$=\prod \limits_{i=1}^{6}{\frac{\left((2k-1)(2k-2) +\frac{1}{2}\right) \cdot \left((2k-1)2k+\frac{1}{2}\right)}{ \left((2k-1)2k+\frac{1}{2}\right) \cdot \left( 2k(2k+1)+\frac{1}{2}\right) }}=$$

$$=\prod \limits_{i=1}^{6}{\frac{\left((2k-1)(2k-2) +\frac{1}{2}\right)}{\left((2k+1)2k+\frac{1}{2}\right)}}=$$

$$=\frac{\frac{1}{2}}{\left(2\cdot3+\frac{1}{2}\right)}\cdot\frac{\left(2\cdot3+\frac{1}{2}\right)}{\left(5\cdot4+\frac{1}{2}\right)}\cdot\frac{\left(5\cdot4+\frac{1}{2}\right)}{\left(7\cdot6+\frac{1}{2}\right)}\cdot ... \cdot\frac{\left(9\cdot8+\frac{1}{2}\right)}{\left(11\cdot10+\frac{1}{2}\right)}\cdot\cdot\frac{\left(11\cdot10+\frac{1}{2}\right)}{\left(13\cdot12+\frac{1}{2}\right)}=$$

$$=\frac{\frac{1}{2}}{\left(13\cdot12+\frac{1}{2}\right)}=\frac{\frac{1}{2}}{\frac{313}{2}}=\frac{1}{313}$$